Economic causes and consequences of terrorism: A study of four Islamic countries / Alam Khan - Alam , Khan (2017)
Terrorism, which has substantially affected economic performance since the start of the new millennium, is a global economic challenge. The Global Terrorism Index (GTI) (2015) reports that terrorism intensity has been concentrated inside Middle East and North Africa (MENA) and Asian economies. Remarkably, only five countries (Afghanistan, Pakistan, Syria, Iraq and Nigeria) account for 78% of deaths due to terrorism. This research develops and applies alternative indicators to examine the economic causes and consequences of terrorism in four Islamic countries, and has four main objectives. First, it investigates the measurement of terrorism at the province level by introducing the Terrorist Economic Impact Evaluation (TEIE) indicator. Second, it examines the poverty and terrorism relationship by extending the TEIE indicator, and it links to the poverty variable at the province level by developing the Poverty Terrorist Evaluation Measurement (PTEM) indicator. Third, it analyzes the trade-terrorism nexus by developing an index of Trade-Terrorist Evaluation Index (TTEI). And fourth, it evaluates the effects of terrorism on economic performance through the Terrorist Attack Vulnerability Evaluation (TAVE) indicator. The findings of the TEIE indicator suggest that terrorism intensity varies across geographical location and time in the case of Islamic countries. The results of TEIE also confirm that geographical dimensions of terrorism matter within a particular economy. Different provinces have different levels and magnitudes of intensity as confirmed from the application of the TEIE indicator. The PTEM indicator is based on the hypothesis that high poverty can generate terrorism. The findings of the PTEM technique on the economy of Pakistan at the provincial level reveal that poverty is the root cause of terrorism. Results of the PTEM technique are also supported by the econometric techniques. The econometric results also support the hypothesis of the PTEM technique and confirm that poverty and terrorism have a long-run and significant relationship. Results of TTEI suggest that terrorism affects international trade in the case of Islamic economies, and these TTEI results are supported by the econometric technique panel autoregressive distributed lag (ARDL) model. The results of the TAVE indicator show that if the real gross domestic product (GDP) growth rate is small, then the total economic leaking caused by an attack always affects economic performance. The economy also experiences a permanent economic desgrowth. On the contrary, if the real GDP growth rate is high, then the total economic leaking caused by a terrorist attack has a limited effect in the beginning stage. Total economic leaking causes economic desgrowth only at a later stage. The application of the TAVE indicator to the Islamic countries demonstrates that economic leakages in the form of economic desgrowth are generated from the economic growth rate caused by terrorism in the case of these Muslim economies. The econometric model results also support those of the TAVE results, and confirm that terrorism has a negative and significant effect on the economic performance of Islamic countries. This study concludes that terrorism can be a cause and consequence in itself.